PREVOCATIONAL TRAINING AND EDUCATION OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN INTEGRATED ENVIRONMENT - Baranauskienė, Ingrida; Jankutė, Milda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Prevocational training and education in integrated environment is especially important for students with special educational needs because it gives them possibility to avoid social exclusion and discrimination in the labour market. In the present article the possibilities of prevocational training and education of students having special educational needs in integrated environment have been analyzed. Specialists’ attitude towards prevocational training and education of students having special educational needs in integrated environment has been revealed; it has been found out how prevocational training and education is performed; factors influencing effective prevocational training and education have been investigated.